GENDER RESPONSIVE EMPOWERMENT STRATEGY FOR SANITATION AND HYGIENE (IUWASH) - Kartikaningrum, Purwaningtyas; Agustina, Isna Fitria (ANTIS PUBLISHER, 2024)
General Background: Sanitation problems remain a challenge in many rural areas, including Larangan Village, Candi District, Sidoarjo Regency. Specific Background: High rates of open defecation (BABS) and minimal access to healthy latrines significantly impact public health and living standards in the village. Knowledge Gap: Despite various programs, strategies that specifically emphasize gender-responsive empowerment in sanitation and hygiene remain underexplored, particularly at the community level. Aims: This research aims to describe and analyze Gender Responsive Empowerment Strategies for Sanitation and Hygiene (IUWASH) implemented in Larangan Village. Results: The research shows that the village government collaborates with USAID to build communal septic tanks and conduct health outreach programs. Residents of Larangan Village actively participate in the IUWASH program through data collection and receiving education on healthy latrines. Additionally, routine inspections are conducted annually by USAID and semi-annually by the village government to ensure sustainability. Novelty: The study highlights the role of community involvement, particularly gender-responsive approaches, in improving sanitation facilities and promoting clean living practices. Implications: The installation of communal septic tanks and ongoing education initiatives successfully increase community awareness and participation, contributing to improved public health and overall welfare in Larangan Village.